The evolution of the racial gap in education and the legacy of slavery - Graziella Bertocchi; Arcangelo Dimico (Institute for the Study of Labor (IZA), 2011)
We study the evolution of racial educational inequality across US states from 1940 to 2000. We show that throughout this period, despite evidence of convergence, the racial gap in attainment between blacks and whites has been persistently determined by the initial gap. We obtain these results with 2SLS estimates where slavery is used as an instrument for the initial gap. The excludability of slavery is preliminarily established by instrumenting it with the share of disembarked slaves from the Trans-Atlantic Slave Trade. Using the same approach we also find that income growth is negatively affected by the initial racial gap in education and that slavery affects growth indirectly through this channel.
urn:nbn:de:101:1-201201104129
Keywords: J15; I24; N31; O11; 330; race; inequality; education; slavery; development; Ethnische Gruppe; Soziale Ungleichheit; Sklaverei; Bildungsverhalten; Einkommen; USA